2019
DOI: 10.1021/acs.est.8b05488
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Variability in Attenuation of Polar Organic Micropollutants in an Urban Lowland Stream

Abstract: Contamination of rivers by trace organic compounds (TrOCs) poses a risk for aquatic ecosystems and drinking water quality. Spatially- and temporally varying environmental conditions are expected to play a major role in controlling in-stream attenuation of TrOCs. This variability is rarely captured by in situ studies of TrOC attenuation. Instead, snap-shots or time-weighted average conditions and corresponding attenuation rates are reported. The present work sought to investigate this variability and factors co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 60 publications
(76 citation statements)
references
References 72 publications
4
71
1
Order By: Relevance
“…Similar concentrations were reported in a parallel study over 2 days (June 14 to June 17, 2016) based on an hourly sampling resolution (comparison provided in Fig. ESM1.I-8) (Jaeger et al, 2019).…”
Section: Oc Concentrations In Surface Watersupporting
confidence: 85%
See 1 more Smart Citation
“…Similar concentrations were reported in a parallel study over 2 days (June 14 to June 17, 2016) based on an hourly sampling resolution (comparison provided in Fig. ESM1.I-8) (Jaeger et al, 2019).…”
Section: Oc Concentrations In Surface Watersupporting
confidence: 85%
“…To date, only few studies have tested these hypotheses. Studies with explicit focus on the fate of OCs in HZs were either conducted in bench-scale flumes (Kunkel and Radke, 2008;Li et al, 2015), in a sediment core of a river bank filtration site (Burke et al, 2014) or insitu river field sites (Jaeger et al, 2019;Radke, 2012, 2011;Lewandowski et al, 2011b;Posselt et al, 2018;Radke et al, 2010;Schaper et al, 2019Schaper et al, , 2018b. In these studies, HZ-like conditions have shown to enhance or induce the biotransformation of certain OCs.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, from the total set of targeted compounds selected as model EOCs, the artificial low-calorie sweetener acesulfame was the most widespread chemical and was detected almost constantly in all polluted streams in our study. This pattern is consistent with previous studies in which acesulfame has been reported as the most ubiquitous EOC in streambed sediments and groundwater across Europe [12,[30][31][32][49][50][51]. Thus, our findings strongly support the use of acesulfame as a marker of EOC pollution for application in management and regulation of surface and subsurface waters [49].…”
Section: Discussionsupporting
confidence: 93%
“…For example, in a bench-scaled flume experiment designed to study hyporheic processes [175], TPs were detected, which were only formed in the sediment but released to the water, hinting at secondary contamination with TPs [176]. In particular, valsartan acid, a rather stable TP of the common blood pressure medication valsartan, forms in situ in the HZ [160,177] and significantly increases its concentrations in the surface water of wastewater receiving streams [178].…”
Section: Retention and (Bio)transformation Of Trace Organic Compoundsmentioning
confidence: 99%